PENGEMBANGAN BUKU AJAR MATA KULIAH BAHASA INDONESIA BERBASIS PEMBELAJARAN KOOPERATIF UNTUK PENGUATAN KARAKTER MAHASISWA FAKULTAS TARBIYAH DAN KEGURUAN UIN STS JAMBI - Yuli Amaliyah (Prodi Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan UIN Sulthan Thaha Saifuddin Jambi, 2022)
This study aims to obtain validity, practicality and attractiveness for the product development of Indonesian language course textbooks based on cooperative learning to strengthen the character of students of the Faculty of Tarbiyah and Teacher Training at UIN STS JAMBI organized into textbooks. The steps taken in this study follow the steps of Model Dick, Carrey & Carrey (2009) which are simplified into nine out of ten steps. The instruments used in this study were the practicality questionnaire ahlim validation questionnaire from peers and the attractiveness test of the students. From the results of the product development feasibility test on the results of the expert validation test, the percentage score was 84.62%, the products that had been developed were very feasible to use. Practical test based on the results of lecturers' responses to the learning module by 91%, products developed in the criteria category are used without revision. In the practicality test through student responses obtained results with an average percentage of 75.16%, the results are at a decent level of qualification.Keywords: Cooperative Learning, Character Education